Exploring Character Personality and Behavioral Dynamics in Biographical Cinema: A Big Five Approach to Milk (2008) - Muhammad Arief Budiman; Maya Kurnia Dewi (Universitas Islam Lamongan, 2025)
This study examines the personality traits of key characters in the biographical film Milk (2008) through the lens of the Big Five personality theory, which includes Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. The research focuses on five central figures—Harvey Milk, Dan White, Anne Kronenberg, Scott Smith, and Mayor George Moscone—to explore how their behaviors, interpersonal interactions, and decision-making reflect distinct personality dimensions. Data were collected through qualitative analysis of character actions, dialogue, and pivotal scenes, followed by categorization according to Big Five traits. The findings reveal significant contrasts among the characters: Harvey Milk demonstrates high openness, conscientiousness, and extraversion, coupled with moderate neuroticism; Dan White exhibits low openness and agreeableness but high neuroticism, explaining his impulsive and destructive behavior; Anne Kronenberg exemplifies organizational competence and emotional stability; Scott Smith shows introversion and moderate neuroticism reflecting personal conflict; and Mayor Moscone illustrates emotional steadiness and cooperative leadership. This study contributes to the understanding of character psychology in biographical cinema, highlighting how personality traits influence both individual behavior and relational dynamics within socio-political contexts. Implications for film studies, psychology, and leadership research are discussed.